The Influence of the Cultural Identity of the Surrounding Community and Social Support on Character Building of Students with the Role of Mediation of External Challenges at the Lgitan Islamic Boarding School, Tuban, East Java - Mochammad Macshoem Faqih; Abid Muhtarom; Abdul Ghofur; Agung Hirmantono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
One of the educational institutions in Indonesia that has its own unique characteristics and differs from other educational institutions is the Islamic boarding school (pesantren). This institution was born, grew, and developed long ago. In fact, since other educational institutions were unknown in Indonesia, pesantren have been present earlier. Therefore, pesantren are generally considered as indigenous Indonesian educational institutions. The community environment, consciously or unconsciously, provides life in all aspects. The research method used was quantitative research, with a sample of 60 13-year-old students at the Langitan Islamic boarding school in Tuban, East Java. The results showed a very strong influence of the community environment on the character education of students. The results of this study confirm that the Cultural Identity of the Surrounding Community Environment does not affect the Character Building of Students at the Langitan Islamic Boarding School, Tuban, East Java. Social Support does not affect the Character Building of Students at the Langitan Islamic Boarding School, Tuban, East Java. The Cultural Identity of the Surrounding Community Environment does not affect the External Challenges of Students at the Langitan Islamic Boarding School, Tuban, East Java. Social Support has a positive and significant effect on the External Challenges of Students at the Langitan Islamic Boarding School, Tuban, East Java. External challenges have a positive and significant effect on the Character Building of Students at the Langitan Islamic Boarding School, Tuban, East Java. External challenges do not mediate the relationship between the Cultural Identity of the Environment and the Character Building of Students at the Langitan Islamic Boarding School, Tuban, East Java. External challenges mediate the relationship between Social Support and the Character Building of Students at the Langitan Islamic Boarding School, Tuban, East Java.